OPTIMIZATION OF THERAPY OF MISCARRIAGE IN PATIENTS WITH ACQUIRED THROMBOPHILIA - Kayumova, D.T.; Sadikova, D.R.; Yunusaliyeva , D.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Spontaneous miscarriage, defined as pregnancy loss before 22 weeks, occurs in 10-20% of clinically recognized pregnancies, most often occurring in the first trimester. Recurrent miscarriage, defined as three or more consecutive pregnancy losses, occurs in 1-2% of women. Although early miscarriage is relatively common, recurrent miscarriage presents unique challenges that require specific treatment strategies. Recurrent miscarriage is often associated with elevated levels of antiphospholipid antibodies (5-15%), sperm DNA damage (up to 85%), and hyperreactive endometrial stromal cells that can accept poor-quality embryos. Materials and Methods: Our review analyzes the literature and guidelines published between 2019 and 2024, defining three main steps: observation, medical therapy, and surgery. The PRISMA method was used to systematically review and extract data from published studies. Results: Hysteroscopic metroplasty has a success rate of 60-85% for women with uterine anomalies. Progesterone therapy may increase the chance of live birth by 20-30% in women with a history of multiple miscarriages. Combination therapy with an anticoagulant and aspirin is more effective than aspirin alone, improving outcomes by 50-60% in women with antiphospholipid syndrome. Conclusion: Effective treatment of recurrent miscarriage involves individualized strategies including surgical correction, hormonal therapy, and immunological management. Evidence supports the use of targeted interventions to significantly improve live birth outcomes.